A study of microbial water quality check and isolation of Helicobacter Pylori from water samples taken from Dhaka city - Rafique, Afra Anika; Sumaiya, Jannatul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.